Malaysia in the IMD World Competitions Yearbook - MPC, (Malaysia Productivity Corporation, 2010)
The Institute for Management Development is based in Lausanne, Switzerland. Since 1989, it has been publishing annually the IMD World Competitiveness Yearbook, which ranks nations according to its competitiveness index. The recent report featured the rankings of 58 economies with Iceland as the latest inclusion to the list. The World Competitiveness Yearbook 2010 (WCY 2010) present competitiveness ranking in four categories is overall scoreboard, ranking by population size, ranking by wealth and ranking by region.